Bridge Quality Appraisal Methodology: Application in The Strimonas Bridge. Case Study - Dimosthenis Kifokeris; Yiannis Xenidis; Panagiotis Panetsos; José António Campos E Matos; Luķs Braganēa (The Baltic Journal of Road and Bridge Engineering, 2018)
In the current utilization of Performance Indicators for bridge  Quality Control, there is no correlation between observed and benchmarked  Performance Indicator values, and an ambiguity of deliverables due to the diverse nature of Performance Indicators. For the alleviation of those above,  this paper presents a methodology that appraises the quality of bridges. This methodology builds on the adaptation of the Sustainable Building Method and its combination with expert input solicitation methods and the research findings of COST Action TU1406. In addition, it features an adaptation of the Analytical  Hierarchy Process. The methodology is presented regarding its general procedural steps and calculating requirements, and then it is tailored to the case study of Strimonas Bridge in Greece.